PRODUCTION OF NITROCELLULOSE FROM CELLULOSE CULTIVATED IN SOUTH KAZAKHSTAN UNDER SUPERCRITICAL CONDITIONS - Ikhsanov Yerbol Saginovich,; Meirbekov Nurkanat Ayazbayuly,; Shalmagambetov Kairzhan Mustafinovich, (Academic Scientific Journal of Chemistry, 2020)
This article presents the results of a study of the process of producing nitrocellulose from Kazakhstani cellulose raw materials using supercritical technology. Nitration can be carried out both directly and indirectly. Direct nitration processes include the reactions of replacing a hydrogen atom by a nitro group or the addition of nitrating agents via a multiple bond, and indirect nitration involves replacing other atoms or groups of atoms with a nitro group (for example, halogens, sulfo groups). Indirect nitration methods include oxidation reactions of nitrogen-containing substances to nitro compounds, as well as condensation reactions leading to nitro compounds. At the same time, the traditional method of nitration of cellulose is quite “dirty” from an environmental point of view, since it spends a huge (several thousand times more than the volume of nitrocellulose obtained) amount of water for the subsequent stage of washing nitrocellulose from nitration mixture residues after nitration. This factor significantly increases the cost of water decontamination and links production to large reservoirs, which is not always possible, especially in arid regions. In addition, due to the relatively small conversion of the nitration process using a nitrating mixture, the production of nitrocellulose requires the construction of large-scale production workshops. Which is also not always justified. Associations with the above are of great interest to alternative nitration technologies, in particular nitration under supercritical conditions. The aim of this work is to study the processes of nitration of cellulose in a supercritical static reactor. For the experiment, the nitration method was chosen in a static supercritical reactor in a carbon dioxide medium using nitric oxide V as a nitrating agent. As a raw material, cotton pulp of the 1st grade was used. The initial reagent for producing nitric oxide V was nitric acid with a concentration of 65% The process was carried out in a static reactor. As a result, a white fibrous mass was obtained, similar in appearance to cellulose, readily soluble in acetone and insoluble in water, the density was 1.63 g / cm³, based on the density, analysis of the melting temperature and the nature of the combustion, we can conclude pyroxylin with a nitrogen content of 12.05 - 12.4%.